Sensor based measurement of ski orientation angles in ski jumping - Kreibich, S.; Müller, S.; Krüger, A. (Science and Skiing V. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2012)
INTRODUCTION: In ski jumping, the v-style as a more effective ski Position superseded the parallel style, because of greater drag und lift forces that is caused when opening the skis (Mroß & Mahnke, 1994; Ito, Seo & Asai, 2008). When opening the ski for the v-style human anatomy produces a tilting of the skis. A greater tilting of the skis reduces the drag und lift forces which can act on them. This interrelation has to be taken into account when trying to optimize the v-style in ski jumping. Previous findings were based on wind channel studies (Kreibich, Mahnke & Müller, 2004) including the v-opening angle, the ski angle of attack and the tilting angle. Under the conditions of a real ski jump only the v-opening angle and the ski angle of attack could be determined by 3D-videophotogrammetry. The application of inertial measurement units (IMU) might overcome that problem. Thus, the aim of this study is to measure the ski orientation angles including the tilting angle in a real ski jumping environment based on IMUs.